DNA barcoding of five common stored-product pest species of genus Cryptolestes (Coleoptera: Laemophloeidae) - Wang, Y J; Li, Z H; Zhang, S F; Varadínová, Z; Jiang, F; Kučerová, Z; Stejskal, V; Opit, G; Cao, Y; Li, F J (Bulletin of entomological research, 2014)
Several species of the genus Cryptolestes Ganglbauer, 1899 (Coleoptera: Laemophloeidae) are commonly found in stored products. In this study, five species of Cryptolestes, with almost worldwide distribution, were obtained from laboratories in China, Czech Republic and the USA: Cryptolestes ferrugineus (Stephens, 1831), Cryptolestes pusillus (Schönherr, 1817), Cryptolestes turcicus (Grouvelle, 1876), Cryptolestes pusilloides (Steel & Howe, 1952) and Cryptolestes capensis (Waltl, 1834). Molecular identification based on a 658 bp fragment from the mitochondrial DNA cytochrome c oxidase subunit I (COI) was adopted to overcome some problems of morphological identification of Cryptolestes species. The utility of COI sequences as DNA barcodes in discriminating the five Cryptolestes species was evaluated on adults and larvae by analysing Kimura 2-parameter distances, phylogenetic tree and haplotype networks. The results showed that molecular approaches based on DNA barcodes were able to accurately identify these species. This is the first study using DNA barcoding to identify Cryptolestes species and the gathered DNA sequences will complement the biological barcode database.
Keywords: brouci; mitochondriální DNA; taxonomické DNA čárové kódování; DNA, Mitochondrial; haplotypy; genetická variace; fylogeneze; Sequence Analysis, DNA; Phylogeny; sekvenční analýza DNA; klasifikace; Haplotypes; Classification; sekvenční seřazení; DNA Barcoding, Taxonomic; Animals; zvířata; Coleoptera; Genetic Variation; Sequence Alignment